Predicting the learning outcomes of students studying for philology degrees based on their approaches to learning - Lungulov Biljana; Milutinović Jovana; Pekić Jasmina (Nastava i Vaspitanje)
In the context of improving the quality of teaching and studies, a considerable amount of research has focused on the differences in the ways students approach learning, which can significantly contribute to achieving learning outcomes. Approaches to learning represent a combination of motivations and strategies students use during the learning process, and they are most commonly categorized into a Surface and a Deep approach. Previous research findings on the relationship between approaches to learning and learning outcomes are inconclusive, and therefore the aim of this study is to examine the relationship between students' approaches to learning, their academic achievement, and course satisfaction. The study involved 180 undergraduates studying for philologydegrees, and used the Revised Two-Factor Study Process Questionnaire (R-SPQ-2F). The obtained results indicate that the Surface approach to learning negatively predicts academic success, while no connection was found between the Deep approach and students' academic achievement. On the other hand, a positive correlation was found between course satisfaction and the Deep approach to learning, both in terms of intrinsic motivation and surface strategy, as well as a negative correlation with the Surface approach to learning in the domain of instrumental motivation. The obtained results are significant for teaching practice, particularly for the purpose of improving teaching and achieving cognitive and affective learning outcomes. Additionally, the findings and conclusions provide guidance on supporting students in applying the Deep approach and strategies in the learning process, as well as on inhibiting the Surface approach to learning.